Jaminan Produk Halal Industri Mikro di Depok Berdasarkan Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal - Fakhriy Ahmad; Muhammad Maksum (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
Indonesian halal product regulation has changed. These arrangements have been in numerous rules, but they have not been binding and strong legal instruments. Halal product assurances in the micro industry, especially in Depok City, are continually failing. Sate Taichan Cihuy and Mie Ayam Pelita Solo production research demonstrates that halal product promises have failed. Doctrinal legal study uses qualitative data for normative legal research. The study examined legislative structure, substance, and culture in relation to the implementation of halal product assurances based on Law Number 33 of 2014. The study found that Indonesia's Halal Product Guarantee Act has inspired a system of regulating halal product guarantees to provide certainty, protection, and guarantees for halal items entering, circulating, and trading in Indonesia. Despite legal clarity, the Halal Product Guarantee Act has been poorly implemented. Micro enterprises, mainly in Depok City, have found food goods without halal certificates. Sate Taichan Cihuy and Mie Ayam Pelita Solo production research. Halal product guarantees have been misimplemented.